Diagnostic accuracy of MRI in diagnosing morbidly adherent placenta, taking intraoperative findings as the gold standard - Malik, Qurat Ul Ain; Ahmed, Nisar; Zeeshan Ali, Muhammad; Ahmed, Saira (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the diagnostic accuracy of magnetic resonance imaging in detecting morbidly adherent placenta in pregnant women with inconclusive ultrasound findings, using intraoperative findings as the gold standard. Method: The cross-sectional study was conducted at the Radiology Department of the Armed Forces Institute of Radiology, Rawalpindi, Pakistan, from January to June 2023, and comprised pregnant females aged 18-40 years having uncertain ultrasound findings and suspicion of morbidly adherent placenta. Magnetic resonance imaging scan of the pelvis was performed with a 1.5 Tesla scanning system on all patients, and findings were noted to compare with operative findings. Sensitivity, specificity, positive and negative predictive values and diagnostic accuracy were calculated for magnetic resonance imaging. Data was analysed using SPSS 23. Results: Among the 14 subjects with a mean gestational age of 32.93±3.36 weeks, both ultrasound and magnetic resonance imaging scan indicated placenta previa in 11(78.6%). Dark intraplacental T2 band was consistently observed in all 14(100%) patients, and complications involving placental separation were noted in 6(42.9%) cases. Magnetic resonance imaging had an accuracy of 85.71% in diagnosing morbidly adherent placenta with 90.9% sensitivity and 66.7% specificity. Conclusion: Magnetic resonance imaging was found to be a valuable diagnostic tool for detecting morbidly adherent placenta, especially in cases with inconclusive ultrasound results. Key Words: Magnetic resonance imaging, Morbidly adherent placenta, Placenta accreta, Placenta previa.